2000
DOI: 10.1038/sj.gene.6363692
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the polymorphism at the heat-shock protein (HSP70-2) gene and systemic lupus erythematosus (SLE) in the Mexican Mestizo population

Abstract: Major histocompatibility complex (MHC) alleles have been recognized as genetic factors for developing systemic lupus erythematosus (SLE). In the present study we analyzed whether a heat-shock protein gene (HSP70-2) is involved in determining susceptibility to develop SLE in a Mexican Mestizo population. A HSP70-2 Pst I polymorphism was detected by a restriction fragment length polymorphism analysis of polymerase chain reaction (PCR-RFLP) in 107 SLE patients and 158 healthy controls. No statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Interestingly, polymorphisms in heat‐shock protein 70 (6p21.3), another Blimp‐1 target gene 1 (ref. 11, and Shaffer A, et al: unpublished observations), have been observed in SLE patients of African American (25) but not Hispanic descent (26). These results suggest that some of the genetic susceptibility to SLE may relate to an enhanced capacity to generate ISCs, although confirmation of this possibility will have to await identification of specific genes that confer SLE risk.…”
Section: Differentiation Of Ig‐secreting Cellsmentioning
confidence: 90%
“…Interestingly, polymorphisms in heat‐shock protein 70 (6p21.3), another Blimp‐1 target gene 1 (ref. 11, and Shaffer A, et al: unpublished observations), have been observed in SLE patients of African American (25) but not Hispanic descent (26). These results suggest that some of the genetic susceptibility to SLE may relate to an enhanced capacity to generate ISCs, although confirmation of this possibility will have to await identification of specific genes that confer SLE risk.…”
Section: Differentiation Of Ig‐secreting Cellsmentioning
confidence: 90%
“…Finally, eleven studies carried out on HLA-DRB1 and -DQB1 polymorphisms in relation to susceptibility to SLE fulfilled inclusion criteria: 1) 9 studies were included in meta-analysis of HLA-DRB1 polymorphism, 2) 6 studies were included in HLA-DQB1 polymorphism analysis and 3) 4 studies were included in haplotype analysis (Table 1). Two of these studies were conducted on Brazilians [7,20], 7 on Mexicans [15][16][17][18][21][22][23], one on Mexican Americans [24] and one on Colombians (current study) (Table 1).…”
Section: Studies Includedmentioning
confidence: 99%
“…23 Minor allele frequencies of many SNPs differ substantially between populations, allowing alleles, when expanded in frequency within one group, more chances to confer greater genetic susceptibility in that one particular population. 24 Examples of ethnic-specific differences in SLE genetic association studies include an association of the p53 gene in Koreans 25 that did not replicate in a Spanish Caucasian population, 26 an association of the heat-shock-protein-encoding gene, HSP70, in Spaniards and Africans but not in Mexicans 27 and the varying levels of significance of CTLA4 associated with SLE in Asians and Europeans. 28 There are even differences in levels of significance within association studies of IRF5 and SLE, such as with studies of Caucasian, 12,14,[17][18][19] Hispanic (Mexican) 15 and Asian subjects.…”
Section: Introductionmentioning
confidence: 99%